PATHOLOGY OF NATURAL LIVER PARASITIC AFFECTIONS IN GOATS - H. Zenad, Khalil; A. Mohammad, Ajwad; A. Abdul Rahman, Rajeha (The Iraqi Journal of Veterinary Medicine, 1996)
This study was designated to evaluate the prevalence of hepatic parasitic lesions in goats and to characterize its pathological (morphological and histo-pathologic) features. Among a total of 1400 examined goats, the prevalence was 15.07 %. Four types of parasitic affections were reported : 1) Fascioliasis (6.4 %), 2) Tennicollosis (5.5 %), 3) Hydatidosis (2.14 %) and 4) Nodular parasitic lesions without identifying the type of parasite (1 %).